Implementation of guidance and counselling services to Muhammadiyah elementary schools, Surakarta, provincial Central Java, Indonesia - Fathoni, Achmad; Muhibbin, Ahmad; Arifin, Zainal; Habiby, Wahdan Najib; Ismail, Mohd Erfy (2021)
Referring to the Minister of Education and Culture’s decree, a guidance and counseling provision or service is really crucial and urgently needed to be implemented in elementary schools. The schools involved principals and class teachers as counselors because they do not have any competent counselor. The subjects of the research were 5 SD Muhammadiyah Elementary Schools in 5 subdistricts of Surakarta. The recent research paper aimed at describing (1) guidance and counseling programs, (2) problems of implementing them, and (3) guidance and counseling problem solving of five SD Muhammadiyah Elementary Schools, Surakarta, Indonesia. A qualitative approach was used. The data collection employed observation, in-depth interviews, and questionnaire techniques. The data were analyzed with an interactive model. The results showed that (1) SD Muhammadiyah Elementary Schools provided guidance and counseling programs. (2) the problems of implementing the guidance and counseling programs were that there were no competent guidance and counseling counselors and insufficient facilities, and (3) the guidance and counseling problem solving was; providing the class teachers knowledge in guidance and counseling, inviting a physiologist to the class teachers’ training and education, providing such facilities as test-instruments, and funding for the programs as part of schools’ budgets.